Using a Teaching Media of “Homophone Stories“ to Improve Students’ Vocabulary Mastery: a Case of Seventh Grade Students at SMPN 1 Kranggan in Academic Year 2014/2015 - Nur Hidayati (Universitas PGRI Semarang, 2015)
The objectives of the study are (1) To find out the students’ vocabulary mastery before being taught by using homophone stories, (2) To find out the students’ vocabulary mastery after being taught by using homophone stories, (3) To find out the significant difference the vocabulary mastery of the seventh grade students of SMP N 1 Kranggan before and after being taught using homophone stories. The population of the study was the seventh grade students of SMP N 1 Kranggan. The writer took class 7D as a sample of the study. The class consists of 31 students. The writer used experimental quantitative research in the study. Test as the instrument was used to collect the data. The objective of conducting try out test was to measure the validity, reliability, discrimination power, and level difficulty of the test. The data was computed and it was find out that 30 items were valid. Then, the valid items were used for the pre-test and post-test of vocabulary mastery item tests. The result of the mean score of students before being taught by using homophone stories was 56.34 and the mean score of students after being taught by using homophone stories was 77.5. The result showed that the mean score of post-test was higher than pre-test. Then, the writer calculated t-test to know whether or not there was significant difference students’ achievement between them who were taught before using homophone stories and students who were taught after using homophone stories. The result showed that t-test was higher than t-table. It was 9.19> 1.697. It means that there is significant difference between the students’ vocabulary mastery after being taught by using homophone stories and before being taught by using homophone stories. From the data above, it can be concluded that the students’ vocabulary mastery after being taught by using homophone stories was higher than the students’ vocabulary mastery before being taught by using homophone stories. The data prove that it is effective to use homophone stories as a media teaching in improving students’ vocabulary mastery.